Repose, Stasis, Rhythm: Walter Pater and James Joyce - Sarbu, Aladár (FOCUS: Papers in English Literary and Cultural Studies, 2002)
It is a fairly reliable indicator ofWalter Pater’s stature that his work is now studied both for its literary-stylistic and its philosophical interest. Oscar Wilde, W. B. Yeats, James Joyce, and Virginia Woolf are all in his debt, and not even those who disliked or thought him harmful, such as T. S. Eliot and Henry James, remained unaffected. His significance reaches well beyond English literary Modernism. J. Hillis Miller, claiming that Pater “is the nearest thing to Nietzsche England has, as Emerson is Nietzsche’s nearest match in America,” calls him one of “the progenitors of modem subjectivistic, ‘impressionistic,’ phenomenological criticism,” and traces a line from Ruskin through Pater and Wilde to Proust, and beyond Proust to Walter Benjamin, Derrida, Paul de Man, and Harold Bloom (Bloom, Walter Pater 75-76). For my part, I will focus attention mainly on aspects of Pater’s influence on Joyce. The lessons of my essay, will, however, have some bearing on the wider literary and philosophical context as well.